The role of textbook learning resources in e-learning: A taxonomic study. (March 2018) - Lau, Kwok Hung; Lam, Tri; Kam, Booi Hon; Nkhoma, Mathews; Richardson, Joan; Thomas, Susan
Abstract: While textbooks are crucial to learning in the traditional classroom-based setting, their role in e-learning environment might be different. Through a categorical analysis, this study investigates if the currently available learning resources provided by textbooks are suitable for e-learning purpose. An e-learning framework incorporating different stages of learning and usage of learning resources was first developed as a guide. Then, a sample of learning resources that came with 100 commonly used textbooks in the disciplines of logistics/supply chain management and information systems were classified using the framework. To corroborate the classification, cluster analysis was also conducted to identify major clusters of learning resources along two dimensions - complexity of content and ease of use. The findings show that most of the sampled textbook learning resources are only suitable for low-order to mid-order learning according to the revised Bloom's taxonomy. The majority of the resources investigated lack the sophistication and complexity to support high-order learning that involves a great deal of interaction and collaboration among learners and facilitators on e-learning platforms. In other words, existing textbook learning resources might contribute well to self-regulated low-order and mid-order e-learning involving basic to intermediate cognitive processes, such as remembering, understanding, applying and analysing. They are generally ill-designed to facilitate high-order e-learning involving advanced cognitive processes, such as evaluating and creating, which require extensive interaction and collaboration among learners and facilitators in an e-learning environment. Highlights: An e-learning framework incorporating usage of learning resources is presented. Learning resources of 100 commonly used textbooks are classified using the framework. Cluster analysis is conducted to corroborate the outcome of the classification. Textbook resources are found mainly suitable for low-order to mid-order e-learning. There is a need for e-learning resources supporting online interaction among peers.